POINT LED LIGHT SOURCES ATTACHED ON THE FEEDERS AND DRINKERS, AS AN ILLUMINATION SYSTEM IN BROILER HOUSES: EFFECTS ON BROILER PERFORMANCE - B. Yeter (Journal of Animal and Plant Sciences, 2020)
The experiment was carried out to evaluate effects of point Light Emitting Diode (LED) lights source attached to the feeders and drinkers on the broiler performance compared with the standard ceiling with the bulb in environment controlled house with two clusters. Total of 3360 chicks were divided into 2 groups (control and experimental) consisting 3 replicates of 560 chicks with 12.5 birds/m2 stocking density. Although, light intensity was measured as 18 lux at the level of feeders for the control group, it was measured 82 lux inside the feeders, 12 lux at the outer edge of them, while the measuring was showing 1 lux at 15 cm distance from the feeders 8 lux at the water dropper and zero in other areas for the experimental group. Standard rearing techniques and commercial diets were used during experimental period and parameters such as growth performance, feed conversion ratio (FCR) and mortality of broiler chicks were determined. The mean chick weight at the beginning of the experiment was similar in the control and experimental groups. There was no difference between lighting applications at the age of first week, however, at later stages, body weight (BW) was recorded significantly higher (P<0.05, P<0.01) in LED illumination treated group compared to control group. No significant differences were observed in feed intake and FCR between lighting treatments. In 42 day old, feed conversion ratios in control and LED lighting treated group were determined as 1.651 and 1.607, respectively (P>0.05). The mortality rates of control and LED lighting treated groups were found to be 5.24 and 3.51 (P<0.05) at the age of 42 days. No negative effect of Point LED lights system on weekly body weight gain, feed intake, and feed conversion ratios were observed, but a positive effect on cumulative body weight and mortality. Therefore, pointed LED can be used as a lighting system in broiler production being cost effective without compromising the productive performance.
Keywords: Broiler; Lighting; Pointed LED; Performance